Urdū adab meṉ maqāmī rang: Urdū fikšan ke ẖuṣūṣī ḥavāle se = Rural Chroma in Urdu Literature : particularly in Urdu Fiction - Hopf, Arian (Buniyād, 2022)
While Hindi literature and many other South Asian literatures are awash with bucolic elements, Urdu seems to be an exception in this regard. Phanishwar Nath Renu’s influential Hindi novel Mailā Ān...
Gesehen am 21.05.2024